SOSIALISASI PENCEGAHAN DAN PENANGANAN PENYAKIT MULUT DAN KUKU (PMK) DI DESA PICISAN TULUNGAGUNG - Zuha Prisma Salsabila; Feriska Achlikul Zahwa; Lillah Servanti Muthi’ah; Nadya Fitri Affifa; Agus Budi Prayogo (Randang Tana - Jurnal Pengabdian Masyarakat, 2023)
This activity aims to provide information about FMD to breeders in Picisan Village, Sendang District, Tulungagung Regency. Picisan village is a village with the majority of the population as breeders. The observation results showed that there were cows infected FMD but only a few cows had been vaccinated. The method of implementing this activity is interactive socialization. The activity was carried out by inviting speaker from the Animal Husbandry Department and the PMK KUD Tani Wilis officer unit. Through this activities, it is hoped that breeders will be able to understand FMD, prevent FMD, participate in FMD vaccination for breeders, and know the proper actions to take when breeders are infected with FMD